Challenges in Teaching Storytelling in a Public Elementary School in the Bicol Region, Philippines - Alimonsurin, Anthony V.; Fuentebella, Reimarl F. (Future Science / FSH-PH Publications, 2025)
Storytelling is a powerful tool for creating attractive learning environments by integrating instructional objectives with activities. This study examines storytelling's effectiveness and implementation challenges at one of the elementary schools in the Bicol Region, Philippines, using qualitative descriptive design and teacher interviews. Findings indicate storytelling deepens critical thinking but faces challenges including students' low comprehension, vocabulary deficits, disengagement, and material scarcity. Interventions like material innovation and community partnerships mitigated these issues. Further research should explore localized storytelling models for Bicol's multilingual classrooms.